Prognostic relevance of combined IDH1 and NPM1 mutations in the intermediate cytogenetic de novo acute myeloid leukemia - Abd El-Lateef, Amal Ezzat; Ismail, Manar M.; Almohammadi, Mohammed; Gawaly, Amr M. (Cellular and Molecular Biology, 2021)
Despite the great advance in treatment, cytogenetically normal Acute myeloid leukemia (CN-AML) is still a challenging entity. The discovery of IDH1 mutation in AML together with the frequent co-mutations; NPM1 and FLT3-ITD throughs a new insight into the pathogenesis and outcome of CN-AML. Recently, there has been an increasing number of recurring mutations in other genes for which the forecasting effect is still required. Despite the large number of risk variables established, there are relatively few prognostic indicators that can help in treatment decisions in AML patients. This study aimed at recording the frequency of IDH1 and NPM1 mutations in newly diagnosed AML and, dual clinicopathological significance. IDH1 and NPM1 mutations were analyzed using High-Resolution Melting curve analysis PCR in 78 newly diagnosed AML patients; 30 pediatric and 48 adult AML patients. IDH1 mutation was detected in 6 out of the 48 adult AML cases (12.5%) and all of them had intermediate cytogenetic prognostic stratification. 5/6 mutant IDH1 patients showed NPM1 co-mutation (P-value= 0.008). Mutant IDH1 patients showed significant resistance to induction therapy (P-value <0.001) and even those who achieved complete remission were relapsed later. Within the intermediate cytogenetic group, the IDH1 mutated patients had short overall survival (HR 12.9, 95% CI (3.1- 53.45) and event-free survival (HR 15.7, 95% CI (2.99-82.72) and P-value <0.001). IDH1 mutation is closely linked to the intermediate cytogenetic stratified group and in particular old age patients and has a great impact on their survival.